Die Prädestinationslehre der Heidelberger Theologen 1583 - 1622 : Georg Sohn (1551 - 1589), Herman Rennecherus (1550 - ?), Jacob Kimedoncius (1554 - 1596), Daniel Tossanus (1541 - 1602) - Lee, Nam Kyu (Reformed historical theology, 2009)
For disputation about the doctrine of predestination the period 1583-1622 is an interesting time for Heidelberg theologians. They regarded the doctrine not as a speculative or curious issue but as the basis for comfort and certainty